â€œKafirlah Hukumnya Orang yang Menyembah Tuhan yang Tiga Ituâ€: Menampik Tuduhan Terkait Problem Doktrin Tritunggal: â€œIt is infidel for those who worship the Three Godsâ€: Dismissing Allegations Regarding the Problem of the Trinity Doctrine - Jatmiko, Yudi (Sekolah Tinggi Teologi SAAT, 2021)
Trinity is a fundamental doctrine in the Christian faith. Though the word â€œtrinityâ€ never appears in the Bible, its truth is displayed throughout the entire writing of the Scripture. However, it does not mean that all people accept this truth. In the Indonesian context, whose major population is Islam, the idea of one God but three and three but one is very polytheistic. Muslims highly regard the concept of monotheism. Standing on this monotheistic truth, to them, the idea of Trinity is not just simply weird but must also be vigorously rejected. Observing the above two facts, the author sees the need for apologetic defense from those accusations. This article exerts to describes allegations concerning the theological and logical problems of the Trinity as well as providing adequate apologetic defense. This article aims to present an objective apologetic defense in the belief that the doctrine of Trinity is monotheistic (theological defense), and even though far surpassing the limited human reasoning, Trinity is not irrational (logical defense).